Internationally trained nurses and host nurses' perceptions of safety culture, work-life-balance, burnout, and job demand during workplace integration: a cross-sectional study - Catharina Roth; Sarah Berger; Katja Krug; Cornelia Mahler; Michel Wensing (BMC, 2021)
Abstract Background The shortage of qualified nurses is a problem of growing concern in many countries. Recruitment of internationally trained nurses has been used to address this shortage, but successful integration in the workplace is complex and resource intensive. For effective recruitment and retention, it is important to identify why nurses migrate and if their expectations are met to ensure their successful integration and promote a satisfying work climate for the entire nursing team. The aim of this study was to examine the perceptions of safety culture, work-life-balance, burnout and job demand of internationally trained nurses and associated host nurses in German hospitals. Methods A multicentric, cross-sectional study was conducted with internationally trained nurses (n = 64) and host nurses (n = 103) employed at two university hospitals in the state of Baden-Wuerttemberg, Germany. An anonymous paper-based survey was conducted between August 2019 and April 2020. The questionnaire included sociodemographic questions, questions regarding factors related to migration, and the German version of the Assessment of your work setting Safety, Communication, Operational Reliability, and Engagement (SCORE) questionnaire. SCORE is divided into three sections: Safety Culture Domains (six subscales), Work-Life-Balance (one subscale), and Engagement Assessment Tool (four subscales). Results Nurses who migrated to Germany were primarily seeking better working conditions, a higher standard of living, and professional development opportunities. Internationally trained nurses reported lower work-related burnout climate (Mean 55.4 (SD 22.5)) than host nurses (Mean 66.4 (SD 23.5)) but still at a moderately high degree (Safety Culture Domains). Host nurses indicated a higher workload (Mean 4.06 (SD 0.65)) (Engagement Assessment Tool) and a lower Work-Life-Balance (Mean 2.31 (SD 0.66)) (Work-Life-Balance) compared to nurses who trained abroad (Mean 3.67 (SD 0.81) and Mean 2.02 (SD 0.86), respectively). No differences were detected for the other subscales. The Safety Culture Domains and Engagement Assessment Tool showed room for improvement in both groups. Conclusion The study suggest that the expectations migrant nurses had prior to migration may not be met and that in turn could have a negative impact on the integration process and their retention. With increasing recruitment of internationally trained nurses from within Europe but also overseas, it is crucial to identify factors that retain migrant nurses and assist integration. Trial registration The study has been prospectively registered (27 June 2019) at the German Clinical Trial Register ( DRKS00017465 ).